Comics as a Media to Understand Earthquake Disaster Mitigation for Elementary School Students: Komik Sebagai Media Untuk Memahami Mitigasi Bencana Gempa Bumi Pada Peserta Didik Sekolah Dasar - Aprianti, Rika; Nadiyyah, Khoirotun; Zakirman; Widiasih (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Community Service held by FKIP-UT at SDN Sukamaju I Cianjur aims to increase students' knowledge about earthquake disaster mitigation. This activity requires media that is appropriate to the level of development of students. Researchers created earthquake disaster mitigation comics as an interesting information medium equipped with colorful illustrations, communicative dialogue and easy to understand for elementary school students. Data collection was carried out quantitatively and qualitatively. Qualitative data was taken from expert input including educational technology lecturers and BNPB staff. Comics are revised based on expert input. Quantitative data was obtained from the results of expert validation tests and a score of 91% was obtained from all aspects including material, media, and language design. Comics were tested during Community Service and were assessed by teachers and students at 92% from all aspects, namely material, media, and language design. This score shows that the comic is suitable for use in the very good category.